2022
DOI: 10.1021/acssuschemeng.2c01742
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Zeolites Active Sites Role as Kinetic Hydrate Promoters: Combined Computational and Experimental Study

Abstract: Clathrate hydrates are emerging as a novel storage medium for safe and compact methane storage. However, their industrial-scale applicability is hindered by relatively lower gas uptake and sluggish formation kinetics. In this study, we have employed zeolites with acidic (H-Y, FAU-type) and basic (Na-X, FAU-type) surface properties as kinetic hydrate promoters (KHPs). The impact of physical parameters as pressure and the gas-to-liquid ratio has also been studied. In a combined experimental and computational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…Such an explanation is also applicable to hydrophilic surface silanol groups and agrees with the literature 76 . However, our previous studies showed that such hydrogen-bonding interactions due to BAS are much lower than that of alkali metal extra framework cations such as sodium which can cause the clathrate structure to collapse 45 .…”
Section: Molecular Level Interaction Of Hydrate Cages With Promotermentioning
confidence: 91%
See 3 more Smart Citations
“…Such an explanation is also applicable to hydrophilic surface silanol groups and agrees with the literature 76 . However, our previous studies showed that such hydrogen-bonding interactions due to BAS are much lower than that of alkali metal extra framework cations such as sodium which can cause the clathrate structure to collapse 45 .…”
Section: Molecular Level Interaction Of Hydrate Cages With Promotermentioning
confidence: 91%
“…Among porous materials, zeolites are green materials with low cost, large surface area, tunable acidity and hydrophobicity, and above all high stability in aqueous medium 42,43 . The above properties of zeolites can significantly affect the kinetics of hydrate formation 44,45 . For example, the zeolite hydrophobicity and acidity can be tuned by changing Si/Al ratio , synthesis conditions or healing the defect sites 46,47 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, these materials can be utilized in two different ways: (1) in low concentrations as a nucleation site for heterogeneous nucleation to reduce the induction time [127] and (2) as host for hydrate using the confinement effect [128]. In the first approach, the porous material increases the surface area by adding another interface (or third surface) that facilitates crystallization and gas diffusion [129]. For example, hollow silica was also examined in many studies and showed kinetic improvement.…”
Section: Methane Storagementioning
confidence: 99%